Influence of new qualitative productivity forces on quality-effective change in China's Yangtze river economic belt sports industry: The mediating effect of industry-University-Research Cooperation. - Xiuqin Chen; Songzhong Ye (PLoS ONE)
Due to the lack of empirical research on the influence of new qualitative productivity forces on quality-effective change in the sports industry, entropy-weighted threshold-based estimation (TOPSIS) is used based on panel data for 11 provinces and cities in China's Yangtze River Economic Belt from 2016-2022. The results are used to measure the levels of new qualitative productivity forces and quality-effective change in the sports industry and to analyze the relationships among these factors and industry-university-research cooperation through a bidirectional fixed effects model and a mediating effects model. The study reveals that new qualitative productivity forces have a significant positive effect on quality-effective change in the sports industry that is heterogeneous by region. Industry-university-research cooperation plays a partially intermediary role in promoting quality-effective change in the sports industry through new qualitative productivity forces. In this context, we propose the following measures: focus on cultivating new-quality industries and strengthening their application in the sports industry, emphasize the intermediary effect of industry-university-research cooperation to promote quality-effective change in the sports industry, formulate strategies according to local conditions, and focus on the development of new qualitative productivity forces in sports.